Solvothermal Synthesis of Gd2O3 : Eu3+ Luminescent Nanowires. (13th June 2010) - Liu, Guixia; Zhang, Song; Dong, Xiangting; Wang, Jinxian
Abstract : Uniform Gd 2 O 3 : Eu 3 + luminescent nanowires were prepared on a large scale by a facile solvothermal method using polyethylene glycol (PEG-2000) as template and ethanol as solvent; the properties and the structure were characterized. X-ray diffraction (XRD) patterns and Fourier transform infrared spectrometry (FTIR) showed that the precursors are hexagonal phase Gd ( OH ) 3 crystals, and the samples calcined at 800C ° are cubic phase Gd 2 O 3 . Transmission Electron Microscopy (TEM) images indicated that the samples are nanowires with a diameter of 30 nm and a length of a few microns. Photoluminescence (PL) spectra showed that the ratio of D 5 0 → F 7 2 to D 5 0 → F 7 1 transition peak of the calcined samples is stronger than that of the precursors, which confirmed that the color purity of the Gd 2 O 3 : Eu 3 + is better than that of the precursors. The as-obtained Gd 2 O 3 : Eu 3 + luminescent nanowires show a strong red emission corresponding to D 5 0 → F 7 2 transition (610 nm) of Eu 3 + under ultraviolet excitation (250 nm), which have potential application in red-emitting phosphors and field emission display devices.